2018
DOI: 10.5539/jfr.v7n4p149
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hygiene Conditions in Sudanese Airlines Catering at Khartoum International Airport

Abstract: Background: Food safety has been recognized as a matter of importance to the airlines industry and airports must have the capacity to ensure a safe environment for passengers using point of entry facilities, including flight catering and other potential risks. The risk of food getting contaminated depends largely on the knowledge and practice of proper food hygiene measures among food handlers. The study aimed to assess the hygiene conditions in airlines catering services units at Khartoum Airport; to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The author defines simultaneous interpretation as the process of interpreting where the interpreter immediately conveys a specific speech from a booth. (See Adam Hamid, 2018).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The author defines simultaneous interpretation as the process of interpreting where the interpreter immediately conveys a specific speech from a booth. (See Adam Hamid, 2018).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Drawing from the reasons theory of accident causation, another contributory factor to major accidents in the workplace is human error [50]. This approach points at the tendency of humans to make errors by their actions under various conditions and situations [53]. From the relevant OHS research in Sudan, several human factors elements have been identified to have played a role towards the level of OHS.…”
Section: Factors Contributing To Poor Ohs and Poor Ohs Research In Sudanmentioning
confidence: 99%